Efficacy of interventions for cutaneous squamous cell carcinoma in situ (Bowen's disease): A systematic review and meta-analysis of proportions - Petzold, Anne; Wessely, Anja; Steeb, Theresa; Berking, Carola; Heppt, Markus (Journal of the European Academy of Dermatology and Venereology, 2024)
Background: Cutaneous squamous cell carcinoma in situ (Bowen's disease) is a precancerous condition confined to the epidermis of the skin. Despite the critical need for effective interventions to halt its progression, there remains a notable shortage of comprehensive data comparing the efficacy of various therapeutic approaches. Objectives: This systematic review and meta-analysis endeavour to compare the different efficacies of interventions by investigating and synthesizing data from numerous trials. Methods: A pre-defined protocol was registered in PROSPERO (CRD42021242224, registration date: 16 April 2021). Systematic searches in Medline, Embase and Central, along with manual trial register searches, identified studies reporting lesion clearance rates (LCR), participant clearance rates (PCR) or recurrence rates (date of last search: 12 June 2024). Quality assessment followed guidelines from the National Heart, Lung, and Blood Institute (NHLBI). After the study arms were categorized into treatment groups and groups of study quality, the proportions were pooled using the generalized linear mixed model (GLMM) as meta-analytical method. Results: A comprehensive inclusion of 71 studies facilitated an evaluation of 3783 lesions for LCR, 1225 patients for PCR, 4073 lesions for lesion recurrence rates (LRR) and 740 patients for participant recurrence rates (PRR). Surgery demonstrated the highest LCR and PCR (0.97, 95% confidence interval (CI): 0.90–0.99) and the lowest LRR (0.04, 95% CI: 0.02–0.07). Conclusions: This study provides a thorough overview of reported efficacy outcomes for practice-relevant interventions for Bowen's disease. Surgery outperformed other treatments for Bowen's disease. For the other intervention groups, it was not possible to show clear differences in effectiveness: LCR, PCR, LRR and PRR showed various treatment rankings, and the comparability was restricted by different numbers of studies between treatment groups and outcome measures, methodical and clinical heterogeneity. Further high-quality studies are needed to investigate practice-relevant interventions for Bowen's disease.
CRIS-Team Scopus Importer:2024-08-23